Small photoalbum, containing photo's of Robeson, his wife and son. Frontpage with text:The Paul Robesons greet you on their Ninth Anniversary London, August 17, 1930. From Goldman-archive, XXIa (1930)
Small photoalbum, containing photo's of Robeson, his wife and son. Frontpage with text:The Paul Robesons greet you on their Ninth Anniversary London, August 17, 1930. From Goldman-archive, XXIa.